PROBLEMS OF PROFESSOR-TEACHER MOTIVATION IN HIGHER EDUCATION INSTITUTIONS AND ITS ANALYSIS (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Academic staff motivation is an important issue for universities seeking to maintain high standards of teaching and research. Academic staff motivation in universities is a complex and multifaceted problem that has a significant impact on the quality of education, research and institutional success. This article sheds light on current problems and obstacles related to the motivation of professors and teachers in higher education institutions.
Keywords: Motivation, encouragement, hierarchy of needs, Expectancy theory, two-factor theory.